2017
DOI: 10.1080/21645515.2016.1232786
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of the safety and immunogenicity of the Tdap vaccine in pregnant Mexican women

Abstract: Immunization with the tetanus, diphtheria, and pertussis (Tdap) vaccine raises controversies on immunogenicity and possible antibody interference. We performed an experimental, double-blind, parallel group controlled clinical trial to evaluate the safety and immunogenicity of the Tdap vaccine in 204 pregnant women and their children and to determine its interference in antibody production. Pregnant women 18 to 38 y of age with 12 to 24 weeks gestation, a low obstetric risk, and without serious disease were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 24 publications
5
42
0
Order By: Relevance
“…However, moderate-to-severe injection site pain was more frequent in pregnant women than nonpregnant women in one study [34]. Injection site reactions assessed over 7 days were more common after Tdap than placebo in one small clinical study [13] but occurred at similar rates over 48 h in another slightly larger study [40]. Systemic and local reactions occurred at similar frequencies in pregnant women receiving Tdap and those receiving tetanus vaccines in two clinical studies [35,36].…”
Section: Vaccine Reactogenicity In Pregnant Womenmentioning
confidence: 94%
See 2 more Smart Citations
“…However, moderate-to-severe injection site pain was more frequent in pregnant women than nonpregnant women in one study [34]. Injection site reactions assessed over 7 days were more common after Tdap than placebo in one small clinical study [13] but occurred at similar rates over 48 h in another slightly larger study [40]. Systemic and local reactions occurred at similar frequencies in pregnant women receiving Tdap and those receiving tetanus vaccines in two clinical studies [35,36].…”
Section: Vaccine Reactogenicity In Pregnant Womenmentioning
confidence: 94%
“…The most commonly reported reactions were injection site reactions, consistent with the Tdap label. While injection site reactions such as pain/tenderness, induration/swelling, itching, and erythema/redness were reported after Tdap/ Tdap-IPV administration in most clinical studies, pregnancy was not considered to have increased the rates of these events [13,34,[36][37][38]40]. However, moderate-to-severe injection site pain was more frequent in pregnant women than nonpregnant women in one study [34].…”
Section: Vaccine Reactogenicity In Pregnant Womenmentioning
confidence: 95%
See 1 more Smart Citation
“…We defined blunting as reported statistically significant lower GMC levels (based on non-overlapping 95% confidence intervals (CI) or p-values) against antigens included in DTaPcontaining vaccines when comparing immunogenicity in infants born to mothers who were vaccinated with Tdap-containing vaccines during pregnancy to a control group (infants born to mothers not exposed to Tdap during pregnancy) after primary immunization and/or booster dose. Of note, several papers reported significant p-values (p < 0.05) with overlapping 95% CI [19][20][21][22][23][24][25]. We adopted the approach to consider these papers as reporting statistically significant lower GMC levels between the two groups and provided point estimates and 95% CI (Table 2) for readers to make their own assessment whether the reported statistical significance refers to a real difference in GMC levels or haphazard reporting.…”
Section: Methodsmentioning
confidence: 99%
“…Nine (out of 11) studies reported significantly lower responses to one or more pertussis antigens after completion of the primary vaccination series in infants whose mothers received Tdap during pregnancy compared to infants whose mothers received no vaccine, placebo, or a non-pertussis-containing vaccine during pregnancy ( Table 2). Seven studies reported significantly lower anti-pertussis toxoid (PT) GMC levels [15][16][17][20][21][22]27,28,30], six studies reported significantly lower anti-filamentous hemagglutinin (FHA) GMC levels [15][16][17]20,21,23,27,30] and five studies reported significantly lower anti-pertactin (PRN) GMC levels [20,22,24,27,30] after primary vaccination. One randomized controlled trial (RCT) from Mexico reported lower responses to PT, after maternal immunization with Adacel (Sanofi Pasteur) and primary vaccination with Pentaxim (Sanofi Pasteur) [22].…”
Section: Pertussis Antigens (Pt Fha Prn)mentioning
confidence: 99%